Community seed banks boost seed, food and nutrition security for thousands in Kenya and Uganda - Vernooy, Ronnie; Otieno, Gloria; Adokorach, Joyce (2024)
Alliance-supported community seed banks in Kenya (since 2019) and Uganda (since 2010) have maintained 72 crop and tree species and more than 600 varieties. Up to September 2023, they distributed 14,100 kg seeds of important food crops, with a value of US$ 36,870. Total sales of seeds and products derived from these crops/trees was US$ 98,530. These activities have provided 2,630 farming households and more than 10,000 individuals with adequate, sustained seed security, and more affordable, diverse, and nutritious foods.